Investigations on the efficacy of some insect growth regulators on anopheles (cellia) balabacensis (Diptera culicidae) - De Las Llagas, Lilian A.
Anopheles balabacensis mosquitoes were exposed to the three Insect Growth Regulators (IGR) ZR 515, PH 6040, and PH 6038, to determine the toxicity and point of action to various life stages of the mosquitoes. The early fourth instar larvae were the most sensitive to ZR 515 and PH 6040. The LC 50 values were 0.00013, 0.00014, and 0.0004 ppm for ZR 515, PR 6040 and PH 6038 respectively. It was observed that the IGR?s produced their effect by blocking metamorphosis and thereby inhibiting adult emergence. Treatment with ZR 515 was the most effective pupae, PH 6040 and PH 6038 on larvae. They tend to delay pupation at least two days if applied on early fourth instar larvae. All of them showed reduction in egg output after treatment with LC 50 concentration of the three IGR?s. Although the IGR?s were less toxic to the early instars they found to interfere with pupa adult transformation and larval-pupal development, causing delayed metamorphosis. Results of the toxicological tests with piperonyl butoxide synergists showed a high degree of synergism. The toxicities increased x 23; x 18; x 16.25 for ZR 515, PH 6040, and PH 6038 respectively.